Gaseous polycyclic aromatic hydrocarbons over the South China Sea: Implications for atmospheric transport under monsoon influences. (June 2023) - Zheng, Haowen; Liu, Mengyang; Lohmann, Rainer; Li, Daning; Vojta, Simon; Katz, Samuel; Wang, Weimin; Ke, Hongwei; Wang, Chunhui; Cai, Minggang
Abstract: The seasonal monsoon variations have significant impact on the atmospheric transport of semi-volatile organic pollutants over the South China Sea (SCS). We analyzed polycyclic aromatic hydrocarbons (PAHs) over the basin and island areas (Yongxing Island and Yongshu Island) in 2017. Gaseous PAHs (0.17–1.4 ng m −3 ) showed spatio-temporal distinctions in their composition and sources among the basin and island areas. Mixed combustion sources of PAHs were identified over the SCS, including a petroleum source near the island areas. The transport routes of PAHs were inferred by the air mass back trajectories and potential source contribution factor analysis, identifying strong biomass burning signals from the Indochina Peninsula and other Southeast Asian countries. Emissions from approximately 90 % of the combustion sources were transported to basin areas by monsoons, whereas the island areas were dominated by local emissions. This study emphasizes the main potential terrestrial source of PAHs over the SCS under monsoon influences. Graphical abstract: Unlabelled Image Highlights: We examined the influence of monsoons on the transport and concentrations of PAHs. Regional biomass burning was identified as a significant source of PAHs. Monsoons produced substantial seasonal variations in PAH concentrations. Emissions were both local and transported from seasonally varying locations.